Multi-stakeholder dialogue space on farmer-led irrigation development in Ghana: an instrument driving systemic change with private sector initiatives - Minh, Thai Thi; Cofie, Olufunke O.; Lefore, Nicole; Schmitter, Petra S. (2020)
Private sector actors bring expertise, resources, and new perspectives to agricultural development, but the tendency to short-term approaches and market-based orientation has been unable to drive a systemic change in the development agenda. We explore how multi-stakeholder dialogues can capitalize on and trickle systemic change through private sector involvement. Analysis from the farmer-led irrigation development multi-stakeholder dialogue space (FLI-MDS) in Ghana shows the need for a physical and institutional space to cater for and merge different stakeholder interests. For all stakeholders, the institutional space is a multi-level-playing institution which can trickle systemic change by leveraging the private sector’s investments with multi-stakeholders’ collaboration, interactive learning, and potential support for commercial scaling of FLI. For private sector actors, a physical space for collaboration is crucial. It enables them to envisage their commercial interests, opening up opportunities for collaboration and mobilization of resources. Ensuring long term sustainability of an FLI-MDS requires catering for the private sector needs for a physical dialogue space to trickle systemic change and accelerate commercialization in farmer-led irrigation development.